Evaluation of spatial differentiation in the Pilsen region from a socioeconomic perspective - Novotná Marie; Šlehoferová Marta; Matušková Alena (Bulletin of Geography. Socio-Economic Series, 2016)
The main objective of this article is to evaluate spatial differentiation in the Pilsen region in the Czech Republic, to create a typology of territorial units, and to evaluate the potential for development and possible threats to development in relation to individual territorial types. To this end, municipal statistical indicators pertaining to population, employment, and economy, were gathered from each of the given territories. The Voronoi map technique was applied to interpolate the values of selected indicators. The typology was created using one of the multivariate statistical methods, namely, the cluster analysis. Furthermore, typological regions and strategies for their development were created.